2019–2020 Florida Citrus Pest Management Guide: Citrus Scab - Megan M. Dewdney (EDIS, 2019)
Citrus scab, caused by the fungus Elsinoë fawcettii, affects grapefruit, Temples, Murcotts, tangelos, and some other tangerine hybrids. There is no need to control citrus scab on processing fruit, except possibly on Temples, where severe early infection reduces fruit size. Reduction or elimination of foliage wetting on susceptible varieties during the active growth period of the fruit will decrease disease severity. This 2-page fact sheet is part of the 2019–2020 Florida Citrus Pest Management Guide. Written Megan M. Dewdney and published by the Plant Pathology Department, March 2019.